Potential for Stem Cell‐Based Periodontal Therapy. Issue 1 (January 2016) - Bassir, Seyed Hossein; Wisitrasameewong, Wichaya; Raanan, Justin; Ghaffarigarakani, Sasan; Chung, Jamie; Freire, Marcelo; Andrada, Luciano C.; Intini, Giuseppe
<x xml:space="preserve">Abstract</x> Periodontal diseases are highly prevalent and are linked to several systemic diseases. The goal of periodontal treatment is to halt the progression of the disease and regenerate the damaged tissue. However, achieving complete and functional periodontal regeneration is challenging because the periodontium is a complex apparatus composed of different tissues, including bone, cementum, and periodontal ligament. Stem cells may represent an effective therapeutic tool for periodontal regeneration due to their plasticity and their ability to regenerate different tissues. This review presents and critically analyzes the available information on stem cell‐based therapy for the regeneration of periodontal tissues and suggests new avenues for the development of more effective therapeutic protocols. J. Cell. Physiol. 230: 50–61, 2016. © 2015 Wiley Periodicals, Inc.